2009
DOI: 10.1002/anie.200900735
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydroaminoalkylation

Abstract: Excellent couplings: Recent developments in the metal-catalyzed C-H activation of sp(3) centers in an alpha position relative to an amine nitrogen atom are presented. Their reaction with alkenes to give alkylamines (hydroaminoalkylation) is also summarized (see general scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(88 citation statements)
references
References 22 publications
5
81
1
1
Order By: Relevance
“…6 It has been shown that N , N - 7 and N , O -chelated early transition metal complexes based on 2-pyridonate, 8 amidate, 9 phosphoramidate 10 and related ligands are active catalysts for the hydroaminoalkylation of olefins with a variety of primary and secondary amines (Scheme 1a). The reactions are widely considered to occur via the initial formation of metal amido intermediates through deprotonation of an N–H bond, 11 therefore limiting the starting materials to primary and secondary amines.…”
Section: Introductionmentioning
confidence: 99%
“…6 It has been shown that N , N - 7 and N , O -chelated early transition metal complexes based on 2-pyridonate, 8 amidate, 9 phosphoramidate 10 and related ligands are active catalysts for the hydroaminoalkylation of olefins with a variety of primary and secondary amines (Scheme 1a). The reactions are widely considered to occur via the initial formation of metal amido intermediates through deprotonation of an N–H bond, 11 therefore limiting the starting materials to primary and secondary amines.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, despite enormous effort within the catalysis community, intermolecular alkene hydroamination catalysis remains very rare and often of unfavorably narrow scope [6]. A recently developed complementary alternative to hydroamination for the catalytic synthesis of amines is the catalytic C-C bond-forming reaction, coined "hydroaminoalkylation", resulting from a C-H bond activation on an sp 3 -hybridized carbon center α to N [7]. This approach formally parallels C-C bond formation α to hydroxyl groups using group 8 and 9 catalysts (typically Ru, Ir based) making use of their activity in transfer hydrogenation [8].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the development of corresponding late transition metal catalyzed amine C-H functionalizations has proven challenging. [92][93][94] Indeed, with the exception of the present authors work, [95][96][97][98][99] all other late transition metal catalyzed hydroaminoalkylations require pyridyl directing groups in combination with mono-olefin reactants. [100][101][102][103][104][105][106][107][108] In a significant departure from prior art, it was found that ruthenium catalyzed hydrogen transfer from 4-aminobutanol to 1-substituted-1,3-dienes results in the generation of dihydropyrrole-allylruthenium pairs, which combine to form products of hydroaminoalkylation with good to complete control of anti-diastereoselectivity (Scheme 18).…”
Section: Hydroaminoalkylationmentioning
confidence: 58%